Thermally modified titania photocatalysts for phenol removal from water - Joanna Grzechulska-Damszel; Antoni W. Morawski; Barbara Grzmil (International Journal of Photoenergy)
Two kinds of titanium dioxide were used as starting materials for thermal modification: Tytanpol A11 supplied by Chemical Factory “Police” S.A. (Poland) and Degussa P25 supplied by Degussa AG (Germany). The photocatalytic activity of titania materials modified by thermal treatment was tested in the reaction of photocatalytic oxidation of phenol. It was found that the highest activity in the reaction of photocatalytic decomposition of phenol, in case of Tytanpol A11, shows the samples of material modified at temperatures of 700 and 750°C. These catalysts were more active than untreated A11, whereas materials modified at higher temperatures show lower activity. In the case of P25, all thermally treated materials were less active than the unmodified material. The photocatalyst samples were characterized by UV-Vis/DR, FTIR/DRS, and XRD methods.